2020
DOI: 10.1016/j.jhin.2020.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Sources of viral respiratory infections in Canadian acute care hospital healthcare personnel

Abstract: Adult to ill household members [7.0, 95% confidence interval (CI) 5.4e9.1], co-workers (3.4, 95% CI 2.4e4.7) or other social contacts (5.1, 95% CI 3.6e7.1). Exposures to patients with respiratory illness were not associated with infection (aOR 0.9, 95% CI 0.7e1.2); however, healthcare personnel with direct patient contact did have higher odds (aOR 1.3, 95% CI 1.1 e1.6). The aORs for exposure and for direct patient contact were similar for illnesses caused by influenza. Conclusion: Community and co-worker conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
(28 reference statements)
0
8
1
Order By: Relevance
“…We found one other study which reported staying in the same HCW break room and eating in proximity to other HCW as risk factor for SARS-CoV-2 transmission [27]. Visiting restaurants other than hospital canteens has previously been shown to be potentially associated with higher risk of SARS-CoV-2 acquisition [26][27][28]; however, this was not the case in our data. This discrepancy could be explained by the fact that i) the visitor turnover of hospital canteens is much higher than in other eating places and ii) that the probability of a HCW being infectious is higher than for an average visitor to other restaurants.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…We found one other study which reported staying in the same HCW break room and eating in proximity to other HCW as risk factor for SARS-CoV-2 transmission [27]. Visiting restaurants other than hospital canteens has previously been shown to be potentially associated with higher risk of SARS-CoV-2 acquisition [26][27][28]; however, this was not the case in our data. This discrepancy could be explained by the fact that i) the visitor turnover of hospital canteens is much higher than in other eating places and ii) that the probability of a HCW being infectious is higher than for an average visitor to other restaurants.…”
Section: Discussioncontrasting
confidence: 87%
“…We identified other work-related COVID-19 risks for HCW. Exposure to ill co-workers is a known risk factor for respiratory illness in HCW, not only for COVID-19 but also for other respiratory viral diseases [ 26 ]. Across all participating institutions, we identified visits to the hospital canteen as potential risk factor for seropositivity.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to ill co-workers is a known risk factor for respiratory illness in HCW, not only for COVID-19 but also for other respiratory viral diseases [22]. Across all participating institutions, we identified visits to the hospital canteen as potential risk factor for seropositivity.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from COVID-19 patients, we identified several easily modifiable occupational factors which might place HCW at increased risk for COVID-19. Exposure to ill co-workers is a known risk factor for respiratory illness in HCW, not only for COVID-19 but also for other respiratory viral diseases 32 . Although this signal was not evident in other HCW cohorts in countries with similar disease burden 14 , it is well conceivable that basic hygiene principles, such as physical distancing or hand hygiene are being neglected in contact with co-workers.…”
Section: An Important Finding Of Our Study Is That Participants Livinmentioning
confidence: 99%
“…The strength and the benefit of healthcare 4.0 adoption has been witnessed in the fight of the novel Coronavirus (COVID-19) pandemic [426]. Coronavirus is one of the viral respiratory illnesses and can be fatal to some immunocompromised patients [427]. However, combating this pandemic has become a global hurdle.…”
Section: Figure 7 Evolution Of Healthcare Systemmentioning
confidence: 99%